2019
DOI: 10.1017/jsi.2019.6
|View full text |Cite
|
Sign up to set email alerts
|

Multiplayer Games: Multimodal Features That Support Friendships of Students With Autism Spectrum Disorder

Abstract: There is an absence of research into online friendships and video gaming activities of students with autism spectrum disorder (ASD). In this article we describe how friendships of students with ASD were developed in an online multiplayer context using the popular sandbox game, Minecraft. Multimodal analysis of the data demonstrated that online multiplayer gaming supported students’ use of speech to engage in conversations about their friendships, and to share gaming experiences with their offline and online fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Many recent research studies have indicated that Autcraft offers neurodiverse players a safe space to participate in positive and meaningful play that integrates social and sensory experiences [82][83][84][85][86][87]. Some specifically reported that the use of speech during the reciprocal conversation (e.g., request, command, initiation) to build friendship and share game experiences further extends positive learning and intervention outcomes [85][86][87]. Social communication is one of the hallmark deficits for neurodiverse individuals.…”
Section: Autcraftmentioning
confidence: 99%
See 2 more Smart Citations
“…Many recent research studies have indicated that Autcraft offers neurodiverse players a safe space to participate in positive and meaningful play that integrates social and sensory experiences [82][83][84][85][86][87]. Some specifically reported that the use of speech during the reciprocal conversation (e.g., request, command, initiation) to build friendship and share game experiences further extends positive learning and intervention outcomes [85][86][87]. Social communication is one of the hallmark deficits for neurodiverse individuals.…”
Section: Autcraftmentioning
confidence: 99%
“…In this virtual environment, players can manipulate particles with different shapes, sizes, and densities to visualize the abstract concept of "social distancing," which can be difficult and risky to teach in a real-world learning environment (e.g., public spaces such as school, museums, and libraries) during a global pandemic. This example demonstrated how an adult stakeholder leveraged the Autcraft platform, reappropriated the conventional play interaction of "building with particles," and offered direct supports to create embedded learning and inclusive play opportunities for neurodiverse players [82][83][84][85][86]91].…”
Section: Autcraftmentioning
confidence: 99%
See 1 more Smart Citation